Liberalismo, colonização e imigração no Brasil Imperial : um estudo sobre a obra Theses sobre colonização do Brasil (1875), de João Cardoso de Menezes e Souza (Barão de Paranapiacaba) - Vieira, Filipe dos Santos (2015)
Our research seeks to understand the immigration thought of João Cardoso de Menezes e Souza, by analyzing the work Theses sobre colonização do Brasil, written in 1875. For comparison and contextualization, we will also analyze the ideas about immigration proposals by contemporary of Menezes e Souza and the historiography about the topic. The ultimate goal is to detect the possible influences and developments of the cited work and also of contemporary writers about immigration, in general, about the process of democratization of some national institutions in the end of nineteenth century, during the transition to Republic.